Spinal Accessory Nerve to Suprascapular Nerve Transfer by Dorsal Approach for Shoulder Reanimation in Cases of Brachial Plexus Injuries: Surgical Technique - Vinita Puri; Raghav Shrotriya; Venkateshwaran N. (Indian Journal of Plastic Surgery)
Distal nerve transfers are frequently used for the treatment of patients having brachial plexus injuries. Spinal accessory nerve to suprascapular nerve transfer by dorsal approach is advantageous since it brings the site of neurotization closer to the neuromuscular end plate and minimizes donor muscle weakness. This surgery is found to be challenging owing to the small and deep operative field. In this article, the authors describe the surgical technique for this procedure.